Brittle faults are weak, yet the ductile middle crust is strong: Implications for lithospheric mechanics. Issue 22 (28th November 2014) - Behr, Whitney M.; Platt, John P.
Abstract A global compilation of shear stress magnitude from mylonites developed along major fault zones suggests that maximum shear stresses between 80 and 120 MPa are reached at temperatures between 300 and 350°C on normal, thrust, and strike‐slip faults. These shear stresses are consistent with estimates of brittle rock strengths based on sliding friction (e.g., Byerlee's law), and with in situ measurements of crustal stress measured in boreholes. This confirms previous suggestions that in some areas at least, the continental crust is stressed close to failure down to the brittle‐ductile transition. Many major active faults in all tectonic regimes are considered to be relatively weak, however; peak static shear stresses for brittle faults estimated by a variety of techniques lie in the range of 1–50 MPa. The sharp contrast between static shear stresses estimated on the seismogenic parts of major faults and those estimated from steady‐state microstructures in ductile rocks immediately below the seismogenic zone suggests that there is an abrupt downward termination, probably controlled by temperature, of the weakening processes that govern fault behavior in the upper crust. These data also imply that seismogenic parts of major fault zones contribute little to lithospheric strength, and are unlikely to have much influence on either the slip rate or the location of the faults. Conversely, ductile middle crust immediately below the brittle‐ductile transition deforms at high stresses, and forms a significant load‐bearing element within the lithosphere.